THE CONSTITUTIONALLY PROTECTED CONTENT ACCORDING TO SECTION 1 OF ARTICLE 5 OF THE CONSTITUTIONAL CODE OF PROCEDURE - Morales Saravia, Francisco (2017)
This  article  will  analyze  the  grounds  of inadmissibility of the amparo process established in paragraph 1 of article 5 of the Peruvian Constitutional Procedural Code. The essential features of the amparo process and the grounds of inadmissibility will be briefly presented. Likewise, reference will be made to doctrinal divergences to define the constitutional content and will be explained by the fact that according to the Fourth Final and Transitional Provision of the Constitution and Article V of the Preliminary Title of the Constitutional Procedural Code, it is possible to configure the constitutional content of a right such as it has done in Constitutional Court of Peru in several cases.